Reputational compliance - Kocziszky, György; Veres Somosi, Mariann; Kobielieva, Tetiana (NTU "KhPI", 2017)
The professional component is methodological in nature, is the core of the model at all levels of government. The communication component of reputational compliance unites the relationships within the collective within the framework of corporate ethics, which is reflected in styles and traditions, formalized with the help of Codes of Corporate Culture and Codes of Professional Ethics and the honor of the organization.
Keywords: organization; model; enterprise